Mitigation of ferroresonance in power system by using FACTS devices - Abdul Malek, Zulkurnain (2012)
Ferroresonance or nonlinear resonance is a type of resonance in electric circuits which occurs when a circuit containing a nonlinear inductance is fed from a source that has series capacitance, and the circuit is subjected to a disturbance such as opening of a switch.